Modern World and the Trend of Human Religiosity: An Overview of Theological Perspective - Duraesa, M. Abzar (Borneo International Journal of Islamic Studies, 2018)
Technological advancement and modernity have a great positive impact for nowadays human life in one hand. But, it might bring some negative dimensions in the other hand. This paper aims at exploring some consequences of modernity, by its technological advancement, to a contemporary human religiosity. Using theological approach and descriptive model of writing scientific papers, this article traces humans’ trend religious behavior by describing a condition of modernization and its relation to some religious and cultural practices. This article finds that people in modern society more have great satisfaction with the use of technological advancement then the use of religious norms. This condicion often makes negative impact of modernization like dehumanization and moral degradation. The findings reveal that religion should becomes primary control of democratization from its normative essence. Spiritual dimension and ethics which are written in Islam and other religions definitely might give optimism in facing disruptive modernization era.